Strong antisymmetric spin–orbit coupling and superconducting properties: the case of noncentrosymmetric LaPtSi. (1st June 2018) - Palazzese, S; Landaeta, J F; Subero, D; Bauer, E; Bonalde, I
Abstract: In this work we aim to analyze the effect of a strong antisymmetric spin–orbit coupling (ASOC) on the superconductivity of noncentrosymmetric LaPtSi. We study the energy gap structure of polycrystalline LaPtSi by using magnetic penetration depth measurements down to 0.02 T c . We observed a dirty s-wave behavior, which provides compelling evidence that the spin-singlet component of the mixed pairing state is highly dominant. This is consistent with previous results in the sense that the mere presence of a strong ASOC does not lead to unconventional behaviors. Our result also downplays LaPtSi as a good candidate for realizing time-reversal invariant topological superconductivity.